Acetylation of MORC2 by NAT10 regulates cell-cycle checkpoint control and resistance to DNA-damaging chemotherapy and radiotherapy in breast cancer. Issue 7 (29th February 2020) - Liu, Hong-Yi; Liu, Ying-Ying; Yang, Fan; Zhang, Lin; Zhang, Fang-Lin; Hu, Xin; Shao, Zhi-Min; Li, Da-Qiang
Abstract: MORC family CW-type zinc finger 2 (MORC2) is an oncogenic chromatin-remodeling enzyme with an emerging role in DNA repair. Here, we report a novel function for MORC2 in cell-cycle checkpoint control through an acetylation-dependent mechanism. MORC2 is acetylated by the acetyltransferase NAT10 at lysine 767 (K767Ac) and this process is counteracted by the deacetylase SIRT2 under unperturbed conditions. DNA-damaging chemotherapeutic agents and ionizing radiation stimulate MORC2 K767Ac through enhancing the interaction between MORC2 and NAT10. Notably, acetylated MORC2 binds to histone H3 phosphorylation at threonine 11 (H3T11P) and is essential for DNA damage-induced reduction of H3T11P and transcriptional repression of its downstream target genes CDK1 and Cyclin B1, thus contributing to DNA damage-induced G2 checkpoint activation. Chemical inhibition or depletion of NAT10 or expression of an acetylation-defective MORC2 (K767R) forces cells to pass through G2 checkpoint, resulting in hypersensitivity to DNA-damaging agents. Moreover, MORC2 acetylation levels are associated with elevated NAT10 expression in clinical breast tumor samples. Together, these findings uncover a previously unrecognized role for MORC2 in regulating DNA damage-induced G2 checkpoint through NAT10-mediated acetylation and provide a potential therapeutic strategy to sensitize breast cancer cells to DNA-damaging chemotherapy and radiotherapy by targeting NAT10.